PENGARUH KETERLIBATAN KERJA, INSENTIF DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT DUAMPANUA DI KABUPATEN PINRANG - JUMARTI, JUMARTI; TIBLOLA, JORDAN; ABIDIN, ZAINAL; Iskandar, Sultan (Patria Artha Management Journal, 2025)
To know and analyze the effect of job involvement, incentives and motivation on the performance of employees at Head Office Duampanuain Pinrang. This research is expected to provide inputs and additional information in making decisions related to the development of institutions, especially in improving the performance of employees. Data used in this study are primary data that the questionnaire answers of respondents with data analysis using multiple linear regression with SPSS 30. The sample in this research is 30 respondents, employees at the Head Office Duampanuain Pinrang. According to the results of analysis showed that all independent variables in the model (simultaneous) effect on employee performance, job involvement variables, incentives and motivation together (simultaneously) has a significant influence on the performance of employees at Head Office Duampanuain Pinrang district .